Load scheduling: challenges and process improvements in food industry inbound logistics - Barbosa, Francisco Tiago Araújo; Mascarenhas, Mauro Sergio Carneiro; Coelho Junior, Luiz Moreira; Peruchi, Rogério Santana (Brazilian Journal of Production Engineering, 2025)
The dairy industry is an important activity for Brazil, generating around 82 billion and responsible for the consumption of a large part of the milk produced in the country. The scheduling of loads for receipt is an important process for the planning of inbound logistics, playing a fundamental role in the performance of the supply chain in dairy products. This study aimed to analyze the process of scheduling loads in a dairy supply chain from January 2024 to December of the same year, to evaluate the performance of suppliers and propose an action plan to solve the identified problems. The methodology was a single case with a qualitative-quantitative approach, exploratory and descriptive objectives, and applied nature. The results show that the lack of scheduling increases operational problems, misuse of resources, people, and operating time, which generate increased costs. They also highlight the lack of communication between customer and supplier, compromising the process. In this way, the establishment of indicators such as the coefficient of variation and the adoption of planned schedules contribute to the optimization of processes and the mitigation of risks, considerably improving the efficiency of inbound logistics.
Keywords: Coefficient of Variation; Inbound Logistics; Goods Receiving; Quality Tools